Homedecor Product Marketing Strategy in Milandbay Restaurant Galery - D Fatimah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to describe Milandbay’s marketing strategy for its home design products. These products from Milandbay are complementary items for home decorations made of bamboo, rattan, wood and so on. Milandbay promotes its products directly by emulating a restaurant gallery. Milandbay’s SWOT analysis approach (which describes strengths, weaknesses, opportunities, and threats) was employed as the study method. The approaches for data collection are carried out are used observation, questionnaires, and in-depth interviews to collect data about products, prices, and promotion tactics. Milandbay has a defined target consumer, diverse and unique products, according to the findings of the SWOT analysis. The issue, on the other hand, is competing in the same product. Milandbay is capable of developing a marketing strategy that introduces visitors to their stores to goods, services, places, services, and experiences. The five points’ strength is also used as an opportunity for Milandbay to develop new products. The ability to introduce their products is aided by social media’s power in promoting products and consumer experiences. Its authenticity will be able to compensate for the weaknesses caused by competition from other brands. It is hoped that by employing this method, marketing strategy decisions will be guided.